Study on the association between the polymorphism of MCP-1 rs1024611 and the genetic susceptibility of type 2 diabetes with sepsis. Issue 32 (12th August 2022) - Li, Yan; He, Junbing; Shao, Yi-ming; Chen, Lanchun; Li, Ming; Tang, Donghui; Shi, Zhizhou; Liao, Qinghui; Guo, Zhongqiu; Wang, Juan; Zheng, Qiaoan; Zhao, Yanni; et al.
Abstract : Monocyte chemoattractant protein-1 (MCP-1) rs1024611 (-2518 A > G) polymorphism are associated with inflammatory diseases. In this study, we investigate the relationship between MCP-1 rs1024611 polymorphism and genetic susceptibility of type 2 diabetes mellitus (T2DM) with sepsis. Two hundred eighty-five patients with T2DM are divided into the diabetes with sepsis group (combined group, 113 cases) and the diabetes group (172 cases). Blood samples and corresponding clinical data were collected. MCP-1 rs1024611 polymorphism in blood samples was detected by pyrosequencing. Meanwhile, the expressions of MCP-1, tumor necrosis factor-alpha (TNF-α), interleukin (IL)-1β, and IL-6 in blood samples were detected by real-time quantitative polymerase chain reaction and enzyme-linked immunosorbent assay, respectively. The relationship between different genotypes of MCP-1 rs1024611 polymorphic locus and T2DM with sepsis was analyzed by combining with the clinical data of the patients. The frequencies of rs1024611 AG/GG genotypes and G allele in T2DM with sepsis group were significantly higher than those in T2DM patients without sepsis ( P  = .004 for AG/GG vs AA genotypes; P  = .037 for G allele vs A allele). Subgroup analysis showed that the rs1024611 G allele frequency in the septic shock group was significantly higher than the general sepsis group ( P  = .02). The expressions of MCP-1 and TNF-α in GG genotypes in T2DM with sepsis group were significantly higher than AA or GA genotypes ( P  < .05). This study preliminarily showed that the rs1024611 A > G polymorphism within the promoter region of MCP-1 gene can upregulate the expression of MCP-1 gene and proinflammatory cytokine TNF-α, which ultimately contributed to the predisposition and progression of T2DM with sepsis.